Refractory angina: what to offer to our patients? - S. N. Tereshchenko; I. V. Zhirov (Кардиоваскулярная терапия и профилактика)
Refractory angina is a relatively rare state that nevertheless remains an important problem in modern cardiology. The article contains its definitions, diagnostics and management algorithms. The emphasis is put on myocardial metabolism modulation as pathogenetic method of refractory angina pharmacotherapy.